Macroeconomics for professionals : a guide for analysts and those who need to understand them - Lipschitz, Leslie; Schadler, Susan (Cambridge : Cambridge University Press, 2019)
Understanding macroeconomic developments and policies in the twenty-first century is daunting: policy-makers face the combined challenges of supporting economic activity and employment, keeping inflation low and risks of financial crises at bay, and navigating the ever-tighter linkages of globalization. Many professionals face demands to evaluate the implications of developments and policies for their business, financial, or public policy decisions. Macroeconomics for Professionals provides a concise, rigorous, yet intuitive framework for assessing a country's macroeconomic outlook and policies. Drawing on years of experience at the International Monetary Fund, Leslie Lipschitz and Susan Schadler have created an operating manual for professional applied economists and all those required to evaluate economic analysis.
Introduction,motivation,and overview -- Real economic activity -- Inflation,relative prices,and expectations -- Monetary policy and accounts -- The fiscal system -- Financial stability -- The external accounts.
Title from publisher's bibliographic system (viewed on 17 Jan 2019).
Keywords: Macroeconomics